PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT RAHAYU PERDANA TRANS CABANG JAKARTA - Lahat, Mohamad Amas; Rst, Rosento; Yulistria, Resti (EDUTECH CONSULTANT, 2019)
The purpose of this study to determine the effect of job stress on employee performance. This study uses quantitative methods with SPSS software version 21. The sample used for data collection amounted to 44 employees using saturated sampling with all the parts in PT Rahayu Perdana Trans Branch Jakarta. The results showed that based on analysis of correlation coefficient test has a significant 2-tailed relationship of 0.746 this means that job stress and employee performance have a strong and direct positive relationship. The coefficient of determination has influence between work stress and employee performance with the result of contribution given equal to 55,7% and the rest influenced by other factor outside this research. And the regression equation shows that every addition of 1 unit of motivation, Y = -26,314 + 1,515X, then there will be addition of 1,515 unit at employee performance. Preferably, PT Rahayu Perdana Trans Branch Jakarta can maintain and motivate employees so that employee performance increases.